Rainfall prediction using multiple inclusive models and large climate indices - Mohamadi S.; Sheikh Khozani Z.; Ehteram M.; Ahmed A.N.; El-Shafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
artificial neural network; computer simulation; error analysis; genetic algorithm; optimization; prediction; rainfall; uncertainty analysis; water management; water resource; Gilan; Iran; Sefidrood Basin; algorithm; climate; hydrology; uncertainty; Algorithms; Climate; Hydrology; Neural Networks, Computer; Uncertainty